An Intelligent Blockchain-based Secure Link Failure Recovery Framework for Software-defined Internet-of-Things - Ali, Jehad; Shan, Gaoyang; Gul, Noor; Roh, Byeong hee (Journal of Grid Computing, 2023)
The frequency of link failures in Internet-of-Things (IoT) network are more than the node failures. Hence, effective link recovery schemes are required for a seamless communication in the IoT. In contrast to traditional networking, the IoT is configured through software-defined networking premise due to its intelligent programmable controller, and orchestration features. SD-IoT with edge computing can help organizations to create a highly flexible and agile IT infrastructure that can adapt quickly to changing business requirements. By automating network operations, optimizing network performance, and improving application availability, SD-IoT can help to improve the efficiency and effectiveness of edge computing environments. Moreover, the security is also a prime issue in the IoT, and DDos attacks are typical threats concerning security in IoT. To combat with these challenges, in this paper we propose a reactive recovery strategy for link failures by proposing a TOPSIS module employing multi-objective-decision making in the intelligent SDN controller, which selects the alternative path for the failed link on the end-to-end (E2E) path in a SD-IoT considering multiple criteria instead of the shortest path only as proposed by the conventional methods for failed link recovery. Moreover, DDoS attacks detection as well as mitigation mechanism based on blockchain in SD-IoT with machine learning is proposed. The blockchain guarantee the security for IoT system. The results demonstrated and validated in Mininet with real SDN controller as well as proof-of-concept experiments in real topologies for IoT shows the effectiveness of the proposed method. Our proposed strategy surpass the traditional schemes in terms of network throughput, recovery delay, and packet delivery ratio.
Keywords: ANN; Block-chain; Edge computing; Intelligent networking; Internet-of-thing network; Multi criteria decision-making; Multicriteria decision-making; Multicriterion decision makings; PCA; Software-defined networkings; ANN; Blockchain; edge computing; fault tolerance; Intelligent networking; IoT network; multi-criteria-decision-making; PCA; Software-defined networking